Bringing out the best in people : How to apply the astonishing power of positive reinforcement - Daniels, Aubrey C. (McGraw-Hill, 2000)
This book is divided into five parts: The perils of traditional management; The astonishing power of positive reinforcement; The scientific approach to leadership; Turning good intentions into high performance; and Revitalizing the workplace.